2017
DOI: 10.1021/acs.jafc.7b00694
|View full text |Cite
|
Sign up to set email alerts
|

Total As and As Speciation in Italian Rice as Related to Producing Areas and Paddy Soils Properties

Abstract: Rice and rice-based foodstuffs are important pathways for inorganic As dietary intake. This work shows a detailed picture of As content and speciation in Italian rice, which contributes to more than one-half of the European production, and addresses the role of soil chemistry and agronomic management on As concentration in rice grain, in view of ameliorative strategies. The mean total As content in Italian white rice was 155 ± 65 μg kg with significant differences among producing areas, while the mean inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Such conclusions, though, may differ by rice type and source, and/or the risk assessment’s underlying assumptions [ 53 , 55 ]. Elevated concentrations of As in grain products, particularly rice-based products, is common, owing to its natural occurrence in soil [ 26 , 53 , 54 , [56] , [57] , [58] , [59] ]. In the most recent FDA TDS, rice and rice-based products were among the products listed with the highest measured As concentrations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conclusions, though, may differ by rice type and source, and/or the risk assessment’s underlying assumptions [ 53 , 55 ]. Elevated concentrations of As in grain products, particularly rice-based products, is common, owing to its natural occurrence in soil [ 26 , 53 , 54 , [56] , [57] , [58] , [59] ]. In the most recent FDA TDS, rice and rice-based products were among the products listed with the highest measured As concentrations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to overestimating the mass of consumption for any specific grain product, this risk assessment also conservatively assumed all As measured in the samples was inorganic, as no differentiation of organic and inorganic As was conducted. Previous researchers have demonstrated that inorganic As represents only a fraction of total As in grain products, including rice-based products, though the fraction of inorganic As ranges widely, depending on the study [ 51 , [56] , [57] , [58] , 61 , 62 ]. FDA estimated that inorganic As could range from 12 % to 100 % of total As in rice and rice products [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, nitrate concentration in the groundwater is almost everywhere contained below 25 L −1 in Piedmont and Lombardy (EU Knowledge Hub Water and Agriculture https://water.jrc.ec.europa.eu/). An emerging constraint is the arsenic (As) concentration in the soils, as rice is an important pathway for inorganic As dietary intake and the rate of As absorption increases with dry‐seeding (Tenni et al, ). However, monitored concentrations are still below the acceptable limits indicated by the EU, and agronomic strategies are being investigated to control and ameliorate food safety (Tenni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging constraint is the arsenic (As) concentration in the soils, as rice is an important pathway for inorganic As dietary intake and the rate of As absorption increases with dry‐seeding (Tenni et al, ). However, monitored concentrations are still below the acceptable limits indicated by the EU, and agronomic strategies are being investigated to control and ameliorate food safety (Tenni et al, ). Considering ecosystems, dry‐seeding could bring some serious drawbacks as traditionally flooded rice paddy fields provide habitat for spring migrants and locally breeding birds (Imperio, Ranghetti, & Hardenberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…That means the chemical speciation of As is more important when explaining the health-related issues than total As level. Rice contains mainly iAs (As-III and As-V) and organic As (dimethyl arsinic acid and monomethyl arsenic acid) (Tenni et al, 2017). For monitoring purposes, European Union (EU/EC 2015) published the regulation for iAs as 0.20 mg/kg for non-parboiled milled rice (i.e.…”
Section: Introductionmentioning
confidence: 99%